Nanomaterial Technology and Soft Tissue Sarcomas - Zhou, Changkai; Chen, Xue; Huang, Ying; Zhang, Qi; Zhu, Shu; Fu, Wei (Frontiers in Oncology, 2022)
Soft tissue sarcomas (STSs) are relatively rare heterogeneous solid tumors of the mesenchymal origin. They account for approximately 1% of all malignant tumors in adults and have more than 70 histological subtypes. Consequently, the rarity and heterogeneity of STSs make their diagnosis and treatment very challenging. Nanotechnology has attracted increasing attention from researchers due to the unique physicochemical and biological properties of nanomaterials with potential medical applications as nanoprobes, drug delivery systems, photosensitizers, radioenhancers, antitumor agents, and their combinations for cancer diagnosis and treatment. This review discusses the progress made in the use of nanotechnology for the diagnosis and treatment of STSs and highlights future prospects of the STS multimodality therapy.